Patriotyzm i ojczyzna w myśli społecznej Józefa Tischnera - Brzechczyn, Krzysztof (Oficyna Wydawnicza Epigram, 2022)
The purpose of this paper is to characterize Józef Tischner’s concept of patriotism and vision of society. I will use four pairs of oppositional categories introduced by Tadeusz Buksiński, namely: individualism — collectivism, intentionalism — contingency, “the depths” — performativness, and rationalism — irrationalism. In my interpretation, Tischner emphasizes the significance of collective beings in social life; an individual, in turn, is described in the categories of intentionalism, rationalism and abyssness.
Keywords: patriotyzm; Solidarność; Tischner; filozofia dialogu; ojczyzna; komunitarianizm; naród; Polska